2014
DOI: 10.1590/1414-431x20143869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical training on liver expression of activin A and follistatin in a nonalcoholic fatty liver disease model in rats

Abstract: Nonalcoholic fatty liver disease (NAFLD) is characterized by fat accumulation in the liver and is associated with obesity and insulin resistance. Activin A is a member of the transforming growth factor beta (TGF)-β superfamily and inhibits hepatocyte growth. Follistatin antagonizes the biological actions of activin. Exercise is an important therapeutic strategy to reduce the metabolic effects of obesity. We evaluated the pattern of activin A and follistatin liver expression in obese rats subjected to swimming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The high-fat diet model has been widely used in previous NAFLD studies (39,40). The histological results of the present study observed NAFLD features in the model rats, indicating that an NAFLD model was successfully generated.…”
supporting
confidence: 66%
“…The high-fat diet model has been widely used in previous NAFLD studies (39,40). The histological results of the present study observed NAFLD features in the model rats, indicating that an NAFLD model was successfully generated.…”
supporting
confidence: 66%
“…In contrast to MSTN, FLST is recognised as an anabolic myokine that blocks the MSTN receptor, subsequently facilitating skeletal muscle hypertrophy (1) . ACVA, a homodimeric glycoprotein produced by the decidua, placenta and fetal membranes, is involved in cellular differentiation, proliferation, remodelling and morphogenesis (31) . FGF-2 is a heparin-binding protein that regulates cellular functions, including muscle regeneration, maintenance and skeletal muscle growth by increasing the proliferation of satellite cells (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Paraformaldehyde-fixed liver sections (5 μm) were stained with hematoxylin-eosin. A semiquantitative histological evaluation [ 18 ] was carried out by two experienced pathologist blinded to the treatment groups to assess the extent of steatosis under light microscope independently (Olympus, Olympus LX70, Japan). The grading ranged 0–3 where 0 = less than 5% of the parenchyma was involved, 1 = 5 to 33%, 2 = 34 to 66%, 3 = more than 66%.…”
Section: Methodsmentioning
confidence: 99%